2016
DOI: 10.1371/journal.pone.0164526
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Prolonged QTc in Sickle Cell Disease

Abstract: Sudden death is a leading cause of mortality in sickle cell disease, implicating ventricular tachyarrhythmias. Prolonged QTc on an electrocardiogram (ECG), commonly seen with myocardial ischemia, is a known risk for polymorphic ventricular tachycardia (VT). We hypothesized that prolonged QTc is associated with mortality in sickle cell disease. ECG were analyzed from a cohort of 224 sickle patients (University of Illinois at Chicago, UIC) along with available laboratory, and echocardiographic findings, and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The SCD cohort with arrhythmia demonstrated a higher odd of in- Indik and colleagues studied two cohorts of SCD and established that a prolonged QT interval and ventricular tachyarrhythmias were significant predictors of mortality in this population. 17 We observed a nearly threefold higher odds of in-hospital mortality among SCD hospitalized patients with arrhythmias as compared to those without arrhythmias on multivariate analysis. In keeping with this finding was a study that suggested that a prolonged QT was an independent predictor of increased sudden deaths in patients with SCD.…”
Section: Odds Of In-hospital Mortality In Scd-related Hospitalizatimentioning
confidence: 61%
See 1 more Smart Citation
“…The SCD cohort with arrhythmia demonstrated a higher odd of in- Indik and colleagues studied two cohorts of SCD and established that a prolonged QT interval and ventricular tachyarrhythmias were significant predictors of mortality in this population. 17 We observed a nearly threefold higher odds of in-hospital mortality among SCD hospitalized patients with arrhythmias as compared to those without arrhythmias on multivariate analysis. In keeping with this finding was a study that suggested that a prolonged QT was an independent predictor of increased sudden deaths in patients with SCD.…”
Section: Odds Of In-hospital Mortality In Scd-related Hospitalizatimentioning
confidence: 61%
“…The reason for the increased frequency of arrhythmias in SCD patients remains largely unclear, but a predilection to cardiac autonomic dysfunction, QT prolongation, and myocardial fibrosis have been posited as possible explanations 15,16 . Indik and colleagues studied two cohorts of SCD and established that a prolonged QT interval and ventricular tachyarrhythmias were significant predictors of mortality in this population 17 . We observed a nearly threefold higher odds of in‐hospital mortality among SCD hospitalized patients with arrhythmias as compared to those without arrhythmias on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant heterogeneity in the rate of development of acute and chronic pain, cerebrovascular disease, acute chest syndrome, 8,9 pulmonary hypertension (PH), diastolic dysfunction, renal failure, hemolytic anemia, and premature or sudden death. [10][11][12][13] Therefore, the development of biomarkers for risk stratification is vital. The utility of such biomarkers in the management of SCD is underscored by their potential application as tools to provide early diagnosis of complications, to identify a subset of individuals at risk for a severe clinical course, to define disease relevant molecular pathways, or to monitor response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 17 It has also been shown to be related to increased serum aspartate transaminase, increased haemoglobin, tricuspid regurgitation velocity and if the ECG was done as an in-patient. 18 Now, patients with SCA and RSH have been shown to have significantly prolonged QTc as compared to controls in this study.…”
Section: Discussionmentioning
confidence: 52%